Geología de los cuadrángulos de Quebrada Mashansha, Raya, La Repartición, Río Inuya, Amasisa y Varadero 21-p. 21-q, 21-r, 22-p, 22-q, 22-r – [Boletín A 110] - Chira Fernández, Jorge Eduardo (1998)
143 p., 6 mapas